IDENTIFIKASI KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPA SISWA SMP NEGERI 1 GLENMORE KABUPATEN BANYUWANGI - Vinandani Meryastiti; Zainur Rasyid Ridlo; Supeno Supeno (Saintifika, 2022)
Critical thinking skills is the ability to reason by using deep reasoning to obtain relevant information or knowledge and be able to draw conclusions or decisions correctly, and accently. Teachers need to know condition of students’ critical thinking skills in order to design appropriate learning designs and can help in the facilitating the increasing of students’ critical thinking skills. Therefore, it is necessary to identify the critical thinking skills of junior high school students in existing science studies. The research method used in this research is decriptive research. The study conducted by identifying students’ critical thinking skills by giving critical thinking skills tests to students of SMPN 1 Glenmore who had taken the concept of energy and energy resources in the Banyuwangi of East Java. The critical thingking skills of SMPN 1 Glenmore students who have taken the concept of energy and energy resources are in the medium category.